KONTRIBUSI KECERDASAN EMOSIONAL TERHADAP HASIL BELAJAR PRAKTEK BATU BETON SISWA DI SMK NEGERI 1 BUKITTINGGI - Lukmanul Hakim Siregar; Dr. Nurhasan Syah, M.Pd (CIVED, 2019)
Abstract— This study aims to find out and reveal how much the contribution of Emotional Quotient to Learning Outcomes of Stone Practices and Concrete of Students at SMK Negeri 1 Bukittinggi. This type of research is descriptive correlational. This research was conducted in the Department of Stone Construction and Concrete Engineering of SMK Negeri 1 Bukittinggi. The population in this study were students of class XI and XII TKBB. Data collection techniques in this study used the questionnaire method. While the Sampling Technique used is Total Sampling. In this study the number of samples was 39 people. The Data analysis techniques were: 1) Descriptive analysis, 2) Normality and Linearity Test, and 3) Hypothesis Test. The results of this study indicate that there is a contribution of Emotional Intelligence to the Learning Outcomes of Stone and Concrete Students at Bukittinggi State Vocational High School 1 with a correlation coefficient of 0.512 and the percentage contribution of Emotional Quotient to learning outcomes is 26.22%..  Keywords: Emotional Quotient, Learning Outcomes, Stone Practices and Concrete.